1992
DOI: 10.1212/wnl.42.11.2181
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked spinomuscular atrophy

Abstract: We studied androgen receptor function in cultured scrotal skin fibroblasts from eight subjects with X-linked spinal and bulbar muscular atrophy (SBMA) (Kennedy's syndrome) from four families. The neuromuscular and endocrine features were similar in all patients. High-affinity dihydrotestosterone binding (Bmax) was decreased in three patients from one family (average, 11.1 fmol/mg) similar to values in subjects with androgen resistance syndromes. Bmax was normal in five SBMA patients from three other families (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 0 publications
2
21
1
Order By: Relevance
“…3,11,14,23 Patients may have signs of androgen insensitivity such as gynecomastia, impotence, and testicular atrophy. 21,25 Our patients previously carried diagnoses that included Kugelberg-Welander disease, amyotrophic lateral sclerosis, hereditary motor and sensory neuropathy, and limb-girdle muscular dystrophy. Despite this, our patients were remarkably homogeneous in their presentations both clinically and electrophysiologically.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,14,23 Patients may have signs of androgen insensitivity such as gynecomastia, impotence, and testicular atrophy. 21,25 Our patients previously carried diagnoses that included Kugelberg-Welander disease, amyotrophic lateral sclerosis, hereditary motor and sensory neuropathy, and limb-girdle muscular dystrophy. Despite this, our patients were remarkably homogeneous in their presentations both clinically and electrophysiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 2 refused the skin biopsy. Warner et al [27] reported a family with 3 brothers with SBMA and a decreased androgen-binding capacity on GSF, whereas in 5 other patients from 3 families the binding capacity was normal. Interestingly, this variable androgen-binding ca pacity is not associated with disparity in neuromuscular and endocrine symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has been shown to be effective in the prevention of gynaecomastia in patients receiving hormonal therapy for prostate cancer [14]. Muscular atrophy can also result from low circulating testosterone levels [15]. …”
Section: Potential Disadvantages Of Long-term Treatmentmentioning
confidence: 99%